Project for Strengthening the Student Profile of Pancasila Centered on Students at Semen Tonasa II Kindergarten - Ashar Ashar; Sadaruddin Sadaruddin; Reski Idamayanti (ARRUS Journal of Social Sciences and Humanities, 2024)
The project to strengthen the profile of Pancasila students is focused on students in facing the challenges of an ever-evolving era. The importance of character formation and Pancasila values at an early age is the main focus of this project. A holistic and participatory approach method is used to strengthen the understanding and implementation of Pancasila values in children's daily lives. An innovative project implemented in the Kindergarten (TK) environment with the main theme "I Love the Earth". This project not only aims to educate children about the importance of protecting the environment, but also focuses on the activity of growing kale as a practical step to create awareness of sustainability and the need for healthy food. The research used qualitative methods and the research subjects consisted of the principal, group B teachers and students. Data collection techniques include observation, interviews and documentation. Then the data was analyzed using the stages used to analyze the data, namely data reduction, data display, and conclusions. The impact of the "I love the earth" project, with the topic of growing kangkum vegetables, includes having faith, being devoted to God Almighty and having noble character, global development, working together, being creative, reasoning critically and being independent. The research results show a significant increase in children's understanding and application of Pancasila values. Parents also reported positive changes in children's behavior and attitudes at home. These findings emphasize the importance of the project to strengthen the profile of Pancasila students at the kindergarten level as a foundation for building strong character at an early age.